Hyoid Bone Position in Patients with Class I and Class III Malocclusion by Using Cone-Beam Computed Tomography - ARIKAN, BÃ¼ÅŸra; DEDEOÄžLU, NUMAN (Journal of Dental School, 2022)
Objectives The hyoid bone has a strategic position in the craniofacial region and has numerous vital functions. This study aimed to assess the hyoid bone position in patients with skeletal class I and class III malocclusion with cone-beam computed tomography (CBCT). Methods The CBCT images of 30 patients with skeletal class I malocclusion and 30 patients with skeletal class III malocclusion were evaluated. The skeletal malocclusion pattern was determined based on the ANB angle. Horizontal, vertical, and angular measurements were made to determine the hyoid bone position on the CBCT images. Independent samples t-test, Mann Whitney U test, and Chi-square test were used for statistical analysis (alpha=0.05). Results While the distances between the hyoid bone and the genial tubercles and the horizontal distance between the hyoid bone and the roof of the nasopharynx were found to be high in class III patients, the angle between the spina nasalis anterior, sella, and hyoid bone (ASH) was observed to be low in class III patients. The distance of the hyoid bone to the posterior nasal spine, its vertical distance from the roof of the nasopharynx, and the length and width of the hyoid bone did not show any significant difference between class I and class III patients. Conclusion The hyoid bone position changed horizontally but not vertically in class III patients. It was also concluded that the hyoid bone dimensions were not affected by skeletal malocclusion.